PENGARUH METODE LATIHAN SIRKUIT DAN METODE KONVENSIONALTERHADAP PENINGKATAN KETERAMPILAN MENGGIRING BOLA - Ferri Hendryanto (STKIP ROKANIA, 2016)
Based on the researchers abservation on the field, the student’s of SSB Tunas Muda Limau Manis Padang still have lack of basic skill of football and control basic of method dribble in football. This research aimed to explain the different effect between sirkuit exercise method and convensional method toward the increasing skill of dribble of student SSB Tunas Muda Limau Manis Padang. This research is quasi experimental research the population of this research was 45student. The sampling techique that used in this research was jenuh sampling techique. So that 30 student’s was choosen. The test used in this research were dribble. Which aimed to know the increasing ability of football at SSB Tunas Muda Limau Manis Padang. Analysis technique that was used in this recearch was t-test. The result of data analysis showed that (1) sirkuit exercise method can increase the student’s dribble of football at SSB Tunas Muda Limau Manis Padang (tobserved 17,98 > t table α=0,05 1,76) (2) convensional method can increase the student’s dribble of football at SSB Tunas Muda Limau Manis Padang (t observed 12,57 > t table α=0,05 1,76) (3) there is significant different between sirkuit exercise method with convensional method toward student’s dribble of football at SSB Tunas Muda Limau Manis padang (t observed 3,74 > t tableα=0,05 1,76).